Analisis Kebijakan Pengenaan Pajak atas Bahan Bakar Minyak Bersubsidi Minyak Solar - Andi M. Iqbal; Roy V. Salomo (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The purpose of this research is to analyze the tax policy on subsidized fuel of diesel oil in Indonesia. Currently, subsidized fuel in Indonesia are taxed Value Added Tax (VAT) by central government and Vehicle Fuel Tax by local government. This research is using post positivist approach with qualitative method of research. The results of this research conclude tax on subsidized fuel oil are taken by goverment with the purpose of revenue productivity for both central governement and local government. Besides, to control the consumption of subsidized fuel in the public. By taxing 2 kind of taxes on subsidized fuel diesel oil incurring the double taxation and resulting those taxes are not neutral for economic since the subsidized fuel are the vital public needs. Government should evaluate the tax policy on subsidized fuel diesel oil by exempting the VAT on subsidized fuel in order to maintain the economic stability and make a strict policy on controlling the consumption on subsidized fuel diesel oil only for them who reserve to get the subsidy.